Rancang Bangun Sistem E-Recruitment Karyawan pada PT Haleyora Powerindo - Tukino Tukino; Amrizal Amrizal (LPPM Universitas Putera Batam, 2020)
Information technology that can be used in this recruitment process is the recruitment of employees for web-based companies, smartphones and so on. e-Recruitment is a system that assists in the recruitment process of employees when selecting employees for recruitment at companies or at certain agencies. With an integrated employee recruitment system it will also make it easier for admins to control applicants who meet criteria and those who do not meet the criteria. Information technology-based e-recruitment can also be implemented for small companies to large companies. A website is a collection of pages that contain information stored on the internet that can be accessed or viewed via the internet network on devices that can access the internet itself such as computers. MySQL is one type of database server that is very popular, this is because MySQL uses SQL as the base language for accessing its database. MySQL is Open Source, this software is equipped with source code (code used to create MySQL), its executable form or code that can be run directly in the operating system UML (Unified Modeling Language) is a language for specification, visualization, building and documentation of an OO (Object-Oriented) based software system.